Caraceterização acústica de salas para prática e ensino musical - Marros, Fernanda (2011)
The musician needs to properly perceive the sound in rooms where it operates, either in an environment designed to be performed or to studying and practice music. For this, it is necessary that these sites are acoustically appropriate, enabling the development and enhancement of musical sound perception. In this study six classrooms of the music school of UFSM were characterized by acoustic impulse response measurements and computer simulation, and considered the user s feedback through questionnaires. The questionnaires enabled to understand the preferences of students and music teachers regarding the acoustic quality of a total of twenty rooms for music practice and teaching. Three study rooms and three collective classrooms were the most cited out of those available for the course, which were evaluated by acoustic impulse response, resulting in achieving specified objectives of the main parameters to assess the acoustic quality of rooms by ISO 3382: 2009. The information provided by the musicians proved to be coherent with the measurement data, as the rooms considered dry had presented reverberation times around 0.4 s, and the rooms considered reverberants had reverberation times (RT) around 1.5 s. The six rooms were characterized as clear and well defined rooms, with values for Clarity ranging between 1.0 and 2.0 dB for live rooms and around 22 dB for dry rooms. The definition has remained above 43% for all rooms with Central Time below 50 ms for rooms of greater clarity and less reverberant, and above 90 ms for the live rooms. In general, most rooms were considered weak in relation to acoustic conditioning, and only two out of twenty rooms were considered adequate by most musicians, without receiving considerable negative criticism, being one a study room with a volume of 79.9 m³ and TR equal to 0.4 seconds, and the other a collective classroom with a volume of 327.85 m³ and TR equal to 1.6 s. The computer simulation was efficient for the prediction of the acoustic behavior of the rooms in study and the data obtained in the simulations were compared to the just noticeable difference (JND) for acoustic parameters investigated (T30, EDT, C80, D50 and Ts). A good correlation was observed between measured and simulated data, particularly for parameters related to noise energy in the frequency range from 63 to 8.000 Hz.